Toxicity of Essential Oils to Diaphania hyalinata (Lepidoptera: Cram bidae) and Selectivity to Its Parasitoid Trichospilus pupivorus (Hymenoptera: Eulophidae) - Silva, Isabel Moreira da; Soares, Marcus Alvarenga; Tavares, Wagner de Souza; Santos, Alexandre dos; Serrao, Jose Eduardo; Vinha Zanuncio, Antonio Jose; Wilcken, Carlos Frederico [UNESP]; Zanuncio, Jose Cola; Sediyama, Carlos Sigueyuki (Oxford Univ Press Inc, 2020)
Diaphania hyalinata (Linnaeus, 1767) is one of the main pests of the cucurbit crops. Biological control and botanicals are used in integrated pest management (IPM), especially in agro-ecological agricultures where the use of synthetic pesticides is restricted.Toxicological effects of plant essential oils on target and nontarget organisms should be evaluated to determine its use in IPM. The toxicity of ginger, peppermint, oregano, and thyme essential oils to D. hyalinata eggs, larvae, and pupae and their selectivity to the parasitoid Trichospilus pupivorus and the LC50, LC99 and the relative selectivity index (RSI) of these botanicals were determined. The eggs of D. hyalinata were more sensitive to the botanicals applied than its larvae and pupae, with higher toxicity of oregano and thyme essential oils, followed by those of peppermint and ginger. Topical application was the least toxic method to D. hyalinata larvae. Ginger, peppermint, and thyme essential oils were more toxic by ingestion and oregano by contact to D. hyalinata larvae.The essential oil concentrations applied to D. hyalinata pupae prevent the emergence of adults of this insect with the oregano essential oil showing the greatest toxicity. Peppermint, ginger, thyme, and oregano essential oils were selective to T. pupivorus with RSI50 of 5.40, 1.38, 8.15, and 6.98 and RSI99 of 1.54, 2.53, 3.90, and 4.16 respectively. The ginger, peppermint, oregano, and thyme essential oils were toxic to immature D. hyalinata and selective to T. pupivorus females presenting potential as an alternative control in the IPM of this pest in Cucurbitaceae crops.
Keywords: biological control; carvacrol; lethal concentration; natural pesticide; relative selectivity index